A Case Report of Expulsion of a 1.1 cms Ureteric Calculus following Homoeopathic Management (Homoeopathy for All, 2026)
Background: Urolithiasis is a common condition  that accounts for a substantial  number of hospital visits. It occurs  when calculi form within the renal  pelvis and subsequently migrate into  other parts of the urinary collecting  system, including the ureters,  bladder and urethra. Case Summary: A case of a right lower ureteric  calculus measuring 1.1 cm,  associated with mild to moderate  hydroureteronephrosis, along with  a small left renal calculus, was  identified on ultrasonography. The  patient presented with pain in both  inguinal regions and reported to the  outpatient department of the Clinical  Research Unit (Homoeopathy),  Dimapur, Nagaland, on 18  September 2019. Based on the  clinical presentation, individualized  homoeopathic treatment was  initiated with Lycopodium clavatum,  followed by Berberisvulgaris Q.  During the course of management,  the patient was monitored clinically  and through relevant investigations. Conclusion: This case documents the clinical  course of ureteric calculus during  homoeopathic management, in  which expulsion of the stone was  observed. As an individual case  report, it does not establish causality  and further systematic studies are  required to evaluate outcomes in  similar clinical conditions.
Keywords: Urolithiasis; Lycopo dium Clavatum; Berberis Vulgaris; Homoeopathy